PRS92 Monument Re-Coordination: Ensuring A United Coordinate System in Baguio City - Giovanni S. Banawa; Mirafe Rhoze A. De Castro; Ranelle S. Gabaig; Maureen A. Guliquey; Martin Angelo D. Lina; Le-An W. Mangsi; Emmanuel T. Romero; Criselda S. Felix (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This research study looked into PRS92 Monument Re-coordination: Ensuring A United Coordinate System in Baguio City. The respondents were composed of thirty locals geodetic engineers who are duly registered with the Geodetic Engineer of the Philippines (GEP), Baguio City Chapter. The descriptive research design and descriptive survey research were the research methodology used. The questionnaire was the main data gathering instrument of the study. Based on the data gathered, the findings are the following: the objectives of re-coordination of PRS92 monuments were very much aware; the initiatives and activities of the PRS92 monument re-coordination were fully implemented, and the challenges met in the implementation of the PRS92 monument re-coordination were very much serious. The conclusions are the following: The high awareness among Geodetic Engineers in Baguio City about PRS92 monument re-coordination underscores their readiness to support the Philippine Reference System 1992 (PRS92); the programs and activities of the PRS92 are still on the process of strengthening its structures and manpower for efficient implementation; and there is a need to address the challenges met in the implementation of the Philippine Reference System 1992.